Las ideas de Anton Szandor Lavey y sus fundamentos en la psicología, el psicoanálisis y el darwinismo social - E. Garcia, Jose (2024)
Beliefs in immaterial or spiritual beings that operate as external agents to alter the course of events and influence human behaviour are very old and have their roots in the pre-civilized history of our species. Among these beliefs are those related to demons and evil entities, which occupy a prominent place, having originated in ancient cultures. They also constitute one of the central dogmas for Christianity. The psychology of religion gave preferential treatment to religious manifestations as a part of human behaviour, but little attention was devoted to beliefs in diabolical entities and their convergent practices. During the 20th century, some intellectual movements developed a cult attitude toward the devil in an increasingly open and explicit way. The publication of The Satanic Bible by Anton Szandor LaVey (1930-1997) and the subsequent evolution that it promoted towards modern Satanism constitutes a milestone of great relevance. LaVey was influenced by diverse sources that led him to conceive the notion of man or humanity which he adopted in his book. In this construction, psychology has played a prominent role, the use of which, as a foundational element, can be considered a form of reception in a context that is completely different from it. The objective of this article was to analyze this reception, the psychological ideas that are recognized in the book, and their influence on LaVey’s global vision of the human being. The study is theoretical and argumentative and does not adopt an evaluative position regarding the entities mentioned.